Mandatory pension savings and long-run debt accumulation: Evidence from Danish register data - Henrik Yde Andersen; Niels Lynggård Hansen; Andreas Kuchler (Danmarks Nationalbank, 2020)
This paper uses two decades of individual level information from Danish administrative registers to show that a 1-dollar increase in pension wealth leads to a 26-cent rise in total debt. We exploit time-sector variation in mandatory pension contribution rates to isolate the effect of pension wealth on the full financial balance sheet. Concerns of confounding factors are mitigated by sampling employees in identical occupations who have worked in the same sectors but at different points in time. Liquidity constraints seem to play a key role, and we couple the crowding-out effect with an increased propensity to use interest-only mortgages.
Keywords: D14; D15; E21; 330; Household debt; Household balance sheets; pension savings